Determination of cepharanthine in rat plasma by LC-MS/MS and its application to a pharmacokinetic study - Yingbin Deng; Weijun Wu; Sunzhi Ye; Wei Wang; Zhiyi Wang (Taylor & Francis Group, 2017)
Context: Cepharanthine (CPA) has been reported to possess a wide range of pharmacological activities. Objective: This study investigates the pharmacokinetic characteristics after oral or intravenous administration of CPA by using a sensitive and rapid LC-MS/MS method. Materials and methods: A sensitive and rapid LC-MS/MS method was developed for the determination of CPA in Sprague-Dawley rat plasma. Twelve rats were equally randomized into two groups, including the intravenous group (1 mg/kg) and the oral group (10 mg/kg). Blood samples (250 μL) were collected at designated time points and determined using this method. The pharmacokinetic parameters were calculated. Results: The calibration curve was linear within the range of 0.1-200 ng/mL (r = 0.999) with the lower limit of quantification at 0.1 ng/mL. After 1 mg/kg intravenous injection, the concentration of CPA reached a maximum of 153.17 ± 16.18 ng/mL and the t1/2 was 6.76 ± 1.21 h. After oral administration of 10 mg/kg of CPA, CPA was not readily absorbed and reached Cmax 46.89 ± 5.25 ng/mL at approximately 2.67 h. The t1/2 was 11.02 ± 1.32 h. The absolute bioavailability of CPA by oral route was 5.65 ± 0.35%, and the bioavailability was poor. Discussion and conclusions: The results indicate that the bioavailability of CPA was poor in rats, and further research should be conducted to investigate the reason for its poor bioavailability and address this problem.